MicroRNA-199a-3p suppresses glioma cell proliferation by regulating the AKT/mTOR signaling pathway - Shen, Liang (Tumour Biol, 2015)
Glioma has been investigated for decades, but the prognosis remains poor because of rapid proliferation, its aggressive potential, and its resistance to chemotherapy or radiotherapy. The mammalian target of rapamycin (mTOR) is highly expressed and regulates cellular proliferation and cell growth. MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene transcription and translation via up-regulating or down-regulating the levels of miRNAs. This study was conducted to explore the molecular functions of miR-199a-3p in glioma. We detected the expression of miR-199a-3p in glioma samples by quantitative PCR (qPCR). Then, we transfected the U87 and U251 cell lines with miR-199a-3p. Cellular proliferation, invasion, and apoptosis were assessed to explain the function of miR-199a-3p. PCR confirmed that the expression of miR-199a-3p was lower in glioma samples combined with normal brain tissues. The over-expression of miR-199a-3p might target mTOR and restrained cellular growth and proliferation but not invasive and apoptosis capability. Results indicated that cellular proliferation was inhibited to regulate the AKT/mTOR signaling pathway by elevating levels of miR-199a-3p. MiR-199a-3p in glioma cell lines has effects similar to the tumor suppressor gene on cellular proliferation via the AKT/mTOR signaling pathway.